Government health expenditures and health outcome nexus: a study on OECD countries - Anwar, Asim; Hyder, Shabir; Mohamed Nor, Norashidah; Younis, Mustafa (Frontiers in Public Health, 2023)
The irresistible increase in health expenditures is an integral part of health policy. The aim of this study is to investigate the impact of health expenditures on health outcome in the OECD countries using data from 1996 to 2020. We used system Generalized Method of Moments (GMM). The findings show that health expenditures have a negative impact on infant mortality while positive on life expectancy. The results further verify that the income measured as GDP, number of doctors and air pollution has a negative effect on infant mortality while these variables has positive effect on life expectancy in the studied countries. The outcome of the study suggests that health expenditures need to be properly utilized and improvements can be made in the health policies to increase the investment in health technology. The government should also focus on measures like economic and environmental to have long lasting health outcome.